Arsenic Concentrations in Well Water and Risk of Bladder and Kidney Cancer in Finland - Kurttio, Päivi; Pukkala, Eero; Kahelin, Hanna; Auvinen, Anssi; Pekkanen, Juha (Environmental health perspectives, 1999)
We assessed the levels of arsenic in drilled wells in Finland and studied the association of arsenic exposure with the risk of bladder and kidney cancers. The study persons were selected from a register-based cohort of all Finns who had lived at an address outside the municipal drinking-water system during 1967-1980 (n = 144,627). The final study population consisted of 61 bladder cancer cases and 49 kidney cancer cases diagnosed between 1981 and 1995, as well as an age- and sex-balanced random sample of 275 subjects (reference cohort). Water samples were obtained from the wells used by the study population at least during 1967-1980. The total arsenic concentrations in the wells of the reference cohort were low (median = 0.1 μg/L; maximum = 64 μg/L), and 1% exceeded 10 μg/L. Arsenic exposure was estimated as arsenic concentration in the well, daily dose, and cumulative dose of arsenic. None of the exposure indicators was statistically significantly associated with the risk of kidney cancer. Bladder cancer tended to be associated with arsenic concentration and daily dose during the third to ninth years prior to the cancer diagnosis; the risk ratios for arsenic concentration categories 0.1-0.5 and ≥ 0.5 μg/L relative to the category with < 0.1 μg/L were 1.53 [95% confidence interval (CI), 0.75-3.09] and 2.44 (CI, 1.11-5.37), respectively. In spite of very low exposure levels, we found some evidence of an association between arsenic and bladder cancer risk. More studies are needed to confirm the possible association between arsenic and bladder cancer risk at such low exposure levels.